THE EFFECT OF CAPITAL STRUCTURE AND SALES GROWTH ON PROFITABILITY IN REAL ESTATE COMPANIES LISTED ON THE IDX FOR THE 2021-2024 PERIOD - Siti Nurhaliza; Munawarah; Juliana Kadang; Nini Andriani (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of capital structure and sales growth on profitability in real estate companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study used a quantitative approach with an explanatory method and a sample of 62 companies selected through purposive sampling, resulting in 248 data observations. Data were analyzed using SPSS version 29. The results showed that capital structure had a negative and significant effect on profitability, while sales growth did not significantly affect profitability. Simultaneously, capital structure and sales growth significantly affected profitability. The research findings indicate that the profitability of real estate companies is more influenced by the company's ability to manage its funding structure than by sales growth. This indicates that increased sales will not necessarily increase profitability if it is not balanced by effective cost management and funding sources.